(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The current paper’s aim is to determine the influence magnitude of the organizational wisdom in achieving strategic foresight for the Daura Refinery plant of the Iraqi Midland Refineries Company (MRC) through the research hypothesis that suggests a lack of impact of organizational wisdom on strategic foresight. The hypothesis was tested using the analytical descriptive method coupled with a questionnaire as the main tool. The 59-article questionnaire was distributed to leaders of the company that comprised the study community; an entirely enclosed group of a non-probability purposive sampling that included (352) individuals, a list that was then narrowed down to (312) as being analytically valid. The study resulted in a number of conclusions on top of which was the existence of influence of significance that the organizational wisdom showed on strategic foresight.